Prolonged Stability of Air-Cathode Microbial Fuel Cell Performance by Inhibiting Aerobic Microbial Growth Using Platinum and Carbon Nanotube (PT-CNT) Nanoparticles as a Cathode Catalyst - Islam, M. Amirul; Chee, Wai Woon; E., Baranitharan; Cheng, C. K.; Yousuf, Abu; Khan, Maksudur R. (UTM Press, 2016)
The inescapable growth of heterotrophic aerobic bacteria on the surface of air cathodes is an important factor causing oxygen depletion and substrate loss thus reduce the performance stability of air cathode single-chamber microbial fuel cells (MFCs). In this study, the possible use of platinum and carbon nanotube (Pt-CNT) nanoparticles as an antimicrobial agents as well as cathode catalyst for air-cathode MFCs was examined. The biomass content on carbon air-cathodes (CACs) was substantially decreased by 38.2% with Pt-CNT treatment after 26 days of MFCs operation. As a result, the oxygen reduction catalytic performance of the Pt-CNT treated CACs was much stable whereas the fast performance decline of the untreated cathode. Consequently, a quite stable electricity production was obtained for the MFCs with the Pt-CNT treated CACs, alternatively with a 22.5% decrease in maximum power density of the MFCs observed with the untreated cathode. Based on these results, it can be concluded that (1) the growth of oxygenconsuming heterotrophic microbes could be inhibited by Pt-CNT, (2) Pt-CNT could be applied as a cathode catalyst for oxygen reduction, thus (4) the MFC with the Pt-CNT -coated cathode led to the enhenced stable current generation.